What clinician's need to know about imaging features in lung cancer? - Binit Sureka; Mahesh Kumar Mittal; Aliza Mittal; Mukul Sinha; Brij Bhushan Thukral (Wolters Kluwer Medknow Publications, 2014)
Bronchogenic carcinoma is one of the most common cancers both in males and females worldwide. Lung malignancies can present with manifestations involving any organ system and also mimic like benign nodules or infective consolidation. Present review highlights spectrum of typical presentations and imaging features of lung malignancies.